A history of Islamic societies - Lapidus, Ira M. (Ira Marvin) (Cambridge : Cambridge University Press, 2014)
This new edition of one of the most widely used course books on Islamic civilizations around the world has been substantially revised to incorporate the new scholarship and insights of the last twenty-five years. Ira Lapidus' history explores the beginnings and transformations of Islamic civilizations in the Middle East and details Islam's worldwide diffusion. The history is divided into four parts. Part I is a comprehensive account of pre-Islamic late antiquity; the beginnings of Islam; the early Islamic empires; and Islamic religious, artistic, legal and intellectual cultures. Part II deals with the construction in the Middle East of Islamic religious communities and states to the fifteenth century. Part III includes the history to the nineteenth century of Islamic North Africa and Spain; the Ottoman, Safavid and Mughal empires; and other Islamic societies in Asia and Africa. Part IV accounts for the impact of European commercial and imperial domination on Islamic societies and traces the development of the modern national state system and the simultaneous Islamic revival from the early nineteenth century to the present.
Title from publisher's bibliographic system (viewed on 30 May 2018).
Keywords: elektronické knihy; electronic books; Islam -- History; Islamic countries -- History